Study on Volume Optimization and Thermal-mechanical CouplingCharacteristics of KRUSTY-HEU Heat Pipe Space Reactor - ZHANG Kaihui, ZHUANG Kun, ZHANG Xinxin, WANG Senshan, DENG Lina, WANG Yongzhan, WANG Yingzhen (Yuanzineng kexue jishu)
Space heat pipe reactors have the advantages of miniaturization, long life, and strong environmental adaptability, and have broad application prospects in the aerospace field. This study focused on a high-enrichment space heat pipe reactor KRUSTY-HEU proposed by Los Alamos National Laboratory. While maintaining the reactivity, the volume was optimized by adding moderator materials to reduce the control rod’s volume and the reflector thickness to decrease spacecraft launch costs and launch loads. In terms of moderator selection, zirconium hydride was selected by comparing the moderator materials commonly used in space reactor with yttrium hydride. For moderator configuration, three schemes including a moderator located inside the core, in the middle, and dispersed in fuel were proposed, and reactivity and safety were analyzed. Three schemes added the same amount of moderator, and the scheme with the largest initial excess reactivity was selected. The results show that the scheme of moderator located inside the core is better than the other two schemes, and the minimum reflector thickness is 8.69 cm, which is 3.11 cm less than before, and the volume is reduced by about 30%. And the reactor remains subcritical state when the control rod is fully inserted and in an unexpected dropping accident. The neutronics and thermal-mechanics were carried out for the optimized scheme. The results show that the fuel temperature has little influence on the reactivity, besides the reactivity do not change with the change of moderator temperature. Moving reflector can control the reactivity effectively, the differential value of the reflector control is highest when the radial reflector moves about 20 cm. The reactivity caused by burnup is small, when the reactor runs for 15 years, the reactivity is basically unchanged, due to the low power of 4.3 kW. During normal operation, the core temperature and thermal displacement are not much different from before, and the maximum thermal stress is about 200 MPa at the interface of moderator and core, which exceeds the yield limit of core material. The thermal stress is effectively reduced to about 63.3 MPa within the yield limit of the material by adding a gap between the moderator and the core. Single pipe failure analysis shows that core temperature, displacement and thermal stress have changed, but it do not affect its safety. In summary, the moderator located inside the core scheme proposed in this study can effectively reduce the volume of KRUSTY-HEU, and the thermal-mechanical coupling characteristics show that the optimized core still has high safety and stability.